Toward an Understanding of the Growth of Ag Filaments on alpha-Ag2WO4 and Their Photoluminescent Properties: A Combined Experimental and Theoretical Study - Longo, Elson [UNESP]; Volanti, Diogo P. [UNESP]; Longo, Valeria M. [UNESP]; Gracia, Lourdes; Nogueira, Icamira C.; Almeida, Marcio A. P. [UNESP]; Pinheiro, Antonio N.; Ferrer, Mateus M.; Cavalcante, Laecio S.; Andres, Juan (Amer Chemical Soc, 2014)
A combined experimental and theoretical study was conducted on the structure and electronic properties of alpha-Ag2WO4 to clarify the nucleation and growth processes of Ag filaments on alpha-Ag2WO4 crystals induced by electron beam irradiation under electron microscopy. X-ray diffraction with Rietveld analysis, micro-Raman and Fourier-transform infrared spectroscopy were used to analyze the structural order/disorder of alpha-Ag2WO4 crystals. These complementary techniques indicated that the microwave-assisted hydrothermal method employed in the synthesis of alpha-Ag2WO4 crystals leads to the freezing of distorted [WO6] and [AgOy] (y = 2, 4, 6 and 7) clusters as the constituent polyhedra of alpha-Ag2WO4 . On the basis of the theoretical and experimental results, we provide a complete assignment of the structure of alpha-Ag2WO4 and describe the relationship among the disorder, nucleation growth, rate of Ag formation, and photoluminescence behavior before and after the irradiation of the accelerated electron beam. Density functional theory (DFT) studies indicated significant changes in the order-disorder of the initial alpha-Ag2WO4 electronic structure, with a decrease in the band gap value from 3.55 to 2.72 eV. The first stages of the electron irradiation on alpha-Ag2WO4 crystal were investigated by DFT calculations, and we have derived a mechanism to describe the formation and growth of Ag filaments during the electronic excitation of the [AgO2] cluster.